Rational design and construction of [Si/SiO2]N one-dimensional photonic crystal for low infrared emissivity and visible light camouflage. (August 2023) - Liu, Yanling; Li, Hongsheng; Tong, Hanxiang; Wu, Aimin; Huang, Hao; Cao, Tun; Ding, Ang
Highlights: The universal photonic crystal model under considering full factors conditions was constructed. The [Si/SiO2 ]N photonic crystal preparation process was optimized through calculation. [S i /S i O2 ]N photonic crystal prepared has an average reflectance of 95.23% in the 3∼5 μm band. [S i /S i O2 ]N photonic crystals achieve different visible colors by variable thickness surface layer. Abstract: A [Si/SiO2 ]N photonic crystal with simplified structure and optimized process was proposed, which achieved good low infrared emissivity and visible light camouflage performance. The universal photonic crystal model was constructed based on the transmission matrix theory and the equivalent interface method. A seven-layer film structure with a central wavelength of 3.750, an optical thickness ratio of 1.150, and Si films as the innermost and outermost layers was determined by simulating the photonic band gap width, location, and reflectivity value. The infrared stealth performance is stable when the incidence angle changes. The infrared spectral deviation due to dispersion, extinction, and film defects can be negligible. The [Si/SiO2 ]N photonic crystals prepared can achieve an average reflectance of 95.23% in the band of 3∼5 μm, and can show five camouflage colors of orange, sandy yellow, dark green, navy blue and purple. This photonic crystal can be used as an ideal stealth material, promising for widespread use in military targets. Graphical abstract: Image, graphical abstract